Cyclic carbonates used in the synthesis of oligocarbonate diols involving step growth polymerization - Rokicki, G.; Kowalczyk, T.; Kozakiewicz, J.; Piotrowska, A. (Polimery, 2022)
The chemical structure of resulting oligocarbonate diols was studied in relation to catalyst type and experimental conditions of the polyesterification of propylene carbonate with 1,6-hexanediol or 1,10-decanediol (Table 1). Unlike ethylene carbonate, propylene carbonate employed as a source of carbonate linkages and n-hexane vised as an azeotroping agent to entrain a 1,2-propane glycol by-product from the reaction medium, afforded products containing practically no polyether moieties. The structure of the resulting carbonate oligomers was studied by MALDI TOF mass spectrometry and ^H and 13C NMR spectroscopies (Figs. 1-9). Of the transesterification catalysts examined, viz., K2CO3, Bu2SnO and tin(II) stearate, Bu2SnO proved to be the best, providing the oligomers terminated exclusively with hydroxyl groups. Such oligomers can be used as polyols to make polyurethanes that are resistant to hydrolysis and oxidation.